High-throughput planar solid-phase extraction coupled to orbitrap high-resolution mass spectrometry via the autoTLC-MS interface for screening of 66 multi-class antibiotic residues in food of animal origin. (30th July 2021) - Mehl, Annabel; Schmidt, Lena J.; Schmidt, Laszlo; Morlock, Gertrud E.
Graphical abstract: Highlights: HTpSPE-autoTLC-HESI-HRMS screening developed for 66 antibiotics of nine classes. The autoTLC-MS interface allowed automated zone elution via simple clicks on target zones. HTpSPE was directly coupled to orbitrap high-resolution mass spectrometry. As proof-of-principle, the method was validated according to EU requirements. Abstract: Antibiotic residues in food pose a major threat to the health of humans and animals worldwide. Their trace-level analysis is still too time- and cost-intensive to be adequately covered in routine analysis. Thus, a new high-throughput planar solid-phase extraction method has been developed for rapid screening of 66 antibiotics. Via simple clicks on the image, the autoTLC-MS interface automatically eluted the target analyte zones directly into an orbitrap high-resolution mass spectrometer operated in the variable data-independent acquisition mode. Muscle tissue, cow milk and chicken eggs were analyzed regarding nine different antibiotic classes, including sulfonamides, diaminopyrimidines, lincosamides, pleuromutilins, macrolides, cephalosporins, penicillins, amphenicols and nitroimidazoles. The planar clean-up took 7 min per sample, which is 5-fold faster than the routine state-of-the-art. The screening method has been validated for one representative of each class according to the European Commission Decision 2002/657/EC. Most analytes were successfully detected at half of their required maximum residue limit.